Troubleshooting of Matrix Frequency Converter Conducted and Radiated Emissions - Asmanis, Gundars; Ribickis, Leonids; Novikovs, Vladimirs (Electrical, Control and Communication Engineering, 2010)
Matrix converter inherently exhibits sinusoidal input current waveforms and has less stressful output voltage waveforms, but it is causing problems with conducted and radiated emissions. This paper deals with matrix converter emitted disturbances from point of view of electromagnetic compatibility (EMC) standard EN61800-3 and allocates the sources of undesirable emissions using standard equipment used for EMC assessment according to variety international EMC standards and discusses methodology of troubleshooting flow, using low cost equipment available in almost every laboratory of Industrial Electronics and Electrical Engineering.